2009
DOI: 10.1513/pats.200806-055rm
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Therapies Revisited: What Have We Learned?

Abstract: Asthma is a heterogenous disorder related to numerous biologic, immunologic, and physiologic components that generate multiple clinical phenotypes. Further, genetic and environmental factors interact in ways that produce variability in both disease onset and severity and differential expression based on both the age and sex of the patient. Thus, the natural history of asthma is complex in terms of disease expression, remission, relapse, and progression. As such, therapy for asthma is complicated and has been a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
2

Year Published

2011
2011
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
3
0
2
Order By: Relevance
“…For example, Martinez and coworkers report that inhaled fluticasone shows sustained (albeit reversible) improvement in the proportion of asthma episode-free days, a reflection of reduced inflammation when compared with a placebo over a 2-year study period (4). Many agents, such as recombinant IL-12 and IFN-g, that specifically target inflammatory cells and their intercellular signaling pathways have not shown similar efficacy to glucocorticoids in human trials (reviewed in 5,6). This argues against the idea that asthmatic inflammation is merely the result of interactions between external stimuli and classic inflammatory cells like eosinophils and T cells.…”
mentioning
confidence: 99%
“…For example, Martinez and coworkers report that inhaled fluticasone shows sustained (albeit reversible) improvement in the proportion of asthma episode-free days, a reflection of reduced inflammation when compared with a placebo over a 2-year study period (4). Many agents, such as recombinant IL-12 and IFN-g, that specifically target inflammatory cells and their intercellular signaling pathways have not shown similar efficacy to glucocorticoids in human trials (reviewed in 5,6). This argues against the idea that asthmatic inflammation is merely the result of interactions between external stimuli and classic inflammatory cells like eosinophils and T cells.…”
mentioning
confidence: 99%
“…While many phenotypes of asthma are recognized, those requiring treatment are not clearly identifiable in very young children, making diagnosis and treatment decisions difficult. Many studies of the natural history of asthma show that in persistent asthma the initial asthma-like symptoms and loss of lung function occur predominately during the first years of life (11,12). This indicates that treatment and diagnostic decisions about asthma in early childhood may be important (11,12), although there is currently insufficient evidence that early treatment improves lung functioning in later life.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies of the natural history of asthma show that in persistent asthma the initial asthma-like symptoms and loss of lung function occur predominately during the first years of life (11,12). This indicates that treatment and diagnostic decisions about asthma in early childhood may be important (11,12), although there is currently insufficient evidence that early treatment improves lung functioning in later life. For example, the Childhood Asthma Management Program (CAMP study) demonstrated that inhaled corticosteroids (ICS) introduced in early childhood do not improve lung functioning in children with asthma, but offer improved control of the disease without serious side-effects (13).…”
Section: Introductionmentioning
confidence: 99%
“…A condição heterogênea na asma inclui episódios agudos que podem ser revertidos espontâneamente ou com tratamento, sintomas persistentes e redução da função pulmonar estão ligados as alterações estruturais que ocorre devido ao processo inflamatório crônico (Lemanske, 2009;Reddel et al, 2009).…”
Section: Definiçãounclassified
“…Os principais fatores que estão ligados ao processo de inflamação e sintomas de hiperreatividade das vias aéreas são: fatores genéticos e ambientais como por exemplos: poeira, alimentos, fármacos, pólen, fungos, insetos, exercício, alterações ambientais e meteorológicas, poluentes atmosféricos, infecções viras e ou bacterianas, irritantes químicos, estresse e vários outros (Hashimoto e Nakahara, 2002;Lemanske, 2009).…”
Section: Definiçãounclassified